Biosynthesis of Gold Nanoisotrops Using Carallia brachiata Leaf Extract and Their Catalytic Application in the Reduction of 4-Nitrophenol - Ahmad Kuthi, Najwa; Chandren, Sheela; Basar, Norazah; Jamil, Mohamad Shazwan Shah (Frontiers in Chemistry, 2022)
The past decade has observed a significant surge in efforts to discover biological systems for the fabrication of metal nanoparticles. Among these methods, plant-mediated synthesis has garnered sizeable attention due to its rapid, cost-effective, environmentally benign single-step procedure. This study explores a step-wise, room-temperature protocol for the synthesis of gold nanoparticles (AuNPs) using Carallia brachiata, a mangrove species from the west coast of Peninsular Malaysia. The effects of various reaction parameters, such as incubation time, metal ion concentration, amount of extract and pH, on the formation of stable colloids were monitored using UV-visible (UV-Vis) absorption spectrophotometry. Our findings revealed that the physicochemical properties of the AuNPs were significantly dependent on the pH. Changing the pH of the plant extract from acidic to basic appears to have resulted in a blue-shift in the main characteristic feature of the surface plasmon resonance (SPR) band, from 535 to 511 nm. The high-resolution-transmission electron microscopy (HR-TEM) and field emission scanning electron microscopy (FESEM) images revealed the morphologies of the AuNPs synthesized at the inherent pH, varying from isodiametric spheres to exotic polygons and prisms, with sizes ranging from 10 to 120 nm. Contrarily, an optimum pH of 10 generated primarily spherical-shaped AuNPs with narrower size distribution (8 – 13 nm). The X-ray diffraction (XRD) analysis verified the formation of AuNPs as the diffraction patterns matched well with the standard value of a face-centered cubic (FCC) Au lattice structure. The Fourier-transform infrared (FTIR) spectra suggested that different functional groups are involved in the biosynthetic process, while the phytochemical test revealed a clear role of the phenolic compounds. The reduction of 4-nitrophenol (4-NP) was selected as the model reaction for evaluating the catalytic performance of the green-synthesized AuNPs. The catalytic activity of the small, isotropic AuNPs prepared using basic aqueous extract was more effective than the nanoanisotrops, with more than 90% of 4-NP conversion achieved in under an hour with just 3 mg of the nanocatalyst.